Humulane-Type Macrocyclic Sesquiterpenoids From the Endophytic Fungus Penicillium sp. of Carica papaya - Wang, Fu-Run; Yang, Li; Kong, Fan-Dong; Ma, Qing-Yun; Xie, Qing-Yi; Wu, You-Gen; Dai, Hao-Fu; Chen, Ping; Xiao, Na; Zhao, You-Xing (Frontiers in Chemistry, 2021)
Three new humulane-type sesquiterpenoids, penirolide A (1), penirolide B (2), 10-acetyl-phomanoxide (3), together with three known compounds aurasperone A (4), pughiinin A (5), and cyclo(L-Leu-L-Phe) (6) were isolated from the endophytic fungus Penicillium rolfsii Y17 derived from the leaves of Carica papaya L. Their structures including their absolute configurations were determined based on the analysis of NMR and HRESIMS spectra, NMR chemical shifts and ECD calculations. Compounds 2, 3, 5, and 6 significantly inhibited glucagon-induced hepatic glucose production, with EC50 values of 33.3, 36.1, 18.8, and 32.1 μM, respectively. Further study revealed that compounds 2, 3, 5, and 6 inhibited hepatic glucose production by suppression glucagon-induced cAMP accumulation.